Bronzealderens keramik – En kilde til forståelse af kommunikation og social interaktion i bronzealderen - Lolk, Julie (Kuml, 2009)
Bronze Age ceramics – A source of information on communication and social interaction in Bronze Age Denmark If not avoided completely, Bronze Age ceramics have generally been dealt with in terms of either Early or Late Bronze Age. Attempts to classify the ceramics within these periods according to ordinary typological conventions have mostly failed. It is therefore argued that Bronze Age ceramics should be viewed in a much broader chronological framework. It is also emphasised that ceramics should be seen in a social context and in relation to functional change. Therefore, all published ceramics from periods I to V from Jutland and Funen have been subjected to an investigation of the chronological and functional implications of groupings in form and attributes (figs. 1-2). As a result, it can be concluded that certain types of vessels that have not previously been classified are diag nostic for periods II-III and IV-V, respectively. Other types of vessels appear sporadically from period II and become frequent from period IV onwards, while yet further types are current during the entire Bronze Age (fig. 3). There is certain agreement with the Swedish A/B-phase partition in the investigated material, such that a Western Danish A-phase can be dated primarily to period IV (with a few exceptional occurrences in the Early Bronze Age), and the B-phase to periods V and VI (with a few occurrences in period IV) (figs. 4-5). Although the A/B-features are chronologically significant there seems to be some overlap between the two phases in Jutland and on Funen, which is also the case in Southern Sweden. It is therefore argued that future research on the subject is necessary and could provide better means of dating Late Bronze Age ceramics (fig. 6). The changing stylistic traits seen in the ceramics at the transition from Early to Late Bronze Age can be considered from a communicational point of view. In proposing this, the European context becomes very relevant. Different levels of similarity between the Continental and the Western Danish ceramics can be pointed out. Cases of very accurate copying and even possible import of foreign vessels are seen in both the Early and Late Bronze Age. But also a more general form of inspiration can be traced. In particular, three themes in vessel shape are omnipresent: Bi-conical vessels, quadri-partite vessels and carinated bowls. Also the tradition of face and house urns is a Pan-European phenomenon. Although some of these Lausitz-inspired vessel types occur sporadically in the Early Bronze Age, European influence on the Danish ceramics tradition seems to become radically more standardised and thorough from period IV onwards. By examining relationships between form and archaeological context it has been attempted to examine the functions of ceramics in a wider perspective. Probable practical functions are discussed briefly on the basis of settlement ceramics, archaeological field observations and general knowledge concerning form and function deduced from ethnographic studies. Attention is drawn to a certain combination of large vessels and smaller cups or bowls that can be recorded in settlement context. It is suggested that this “set” represents storage vessels and individual service. The function of ceramics in relation to burial practice is also discussed. Through comparison of ceramics from settlements and graves it can be stated that grave ceramics in both the Early and Late Bronze Age represent a wide range of vessel types. In contrast, certain types do not occur at settlements, for example, the three Lausitzinspired shape themes bi-conical, quadripartite vessels and carinated bowls in the Early Bronze Age, and face urns and house urns in the Late Bronze Age. Ceramics form a part of the formal transition from inhumation to cremation and urn graves. Apparently, proportional factors were dominant when it came to choosing a vessel for burial. Primarily small beakers were chosen for inhumation and, not surprisingly, large vessels were used as urns, combined with bowls placed upside down as lids. In cremation graves without urns, ceramics were used in much the same way as in inhumation graves. Also the earliest urn graves seem to reflect a transitional phase bet ween different uses of ceramics (fig. 7). The small vessels in the Early Bronze Age inhumation graves could be seen as being linked to a general drinking cult related to burial rites as has been suggested for cups made of other materials, e.g. bronze and gold. This possible drinking cult clearly has European implications. Additionally, it seems that vessels in Early Bronze Age inhumation graves were primarily a masculine privilege as was also the case with other kinds of containers. On the other hand, the earliest ceramic urns seem to have been reserved entirely for women and children as far as can be concluded from the sparse evidence. The latter brings to mind the fact that the earliest cremation graves on the Continent are likewise those of women. The combination of large vessels and bowls that can be seen in both settlement- and grave assemblages also seems to have its roots in Continental practising of the urn-grave custom (fig. 8). Bronze Age society is often regarded as an exogamic and patriarchal tribal system. Cases of women buried with a complete set of equipment originating from a different region to that in which they were interred are normally interpreted as evidence of intermarriage and alliances between distant tribes. Five very similar vessels have been found dispersed from Hammah, near Hamburg, through Northern Germany to the southwestern and eastern coasts of Jutland and as far as Thy in Northern Jutland. It is an interesting thought to see these as an expression of related women married into different regions passing on a certain ceramic tradition. It is proposed that potters in the Early Bronze Age were very much at liberty to express themselves in creating vessels, being limited only by the broad conventions implied in bodily rooted patterns shared by cultural groupings (so called Motor Habits). Early sporadic occurrences of certain vessel types from period II onwards can be seen within this framework. The changes, which ceramics underwent between periods III and IV, seem rather radical and must be explained in another way. Inspired by Pierre Bourdieu, an attempt has been made to connect different kinds of “symbolic capital” to the ceramics. It is argued that ceramics have more to do with the domestic sphere and the changes in burial customs than with prestige and political alliances in a classical sense. Ceramics and urn burials could also be connected with the female sex. It has previously been documented that there could have been a change in the status of the female gender during the Bronze Age (figs. 9-12). It is therefore stated that the development in pottery tradition, towards new vessel types and a higher degree of standardisation and possibly specialisation, should be seen in the light of a new role in society for the female gender, implying new ritual and social skills internally on the settlements, and in external communication. Using Michael B. Shiffer’s thoughts on communication and material culture, it is recommended to focus attention on the receiving part in a communication process. In this way the transformations in ceramic production between the Early and Late Bronze Age can be seen as an expression of changing associations in the mind of the receiver. Vessels in the Early Bronze Age might only have signalled individual factors, whereas ceramics in the Late Bronze Age were associated with certain Pan-European conventions connected to burial customs and women. The standardisation of the ceramic production and higher degree of similarity in vessel shape and ornamentation across large geographical areas might indicate a different kind of group identity, at least for female potters. Such identification can happen “down the line” between small local groups, or it can involve some sort of imagined community over larger areas. In addition, an attempt has been made to sketch a possible cognitive framework behind the perception and use of ceramics in the Bronze Age. It is suggested that Early Bronze Age use of grave ceramics reflects a tradition where the vessel is a container either for provisions on the journey to an after-world or for ritual consumption during burial. The urn in the Late Bronze Age, on the other hand, can be seen as a metaphorical house and/or likewise metaphorical body for the remaining part of a pluralistic soul, while the bowl could be a symbolic roof and/or head on the “urn house/body”. These deduced connotations may to some extent have formed common ground in large communities as variations on a theme. Finally it is stated that synthetic studies such as this are sometimes necessary in order to move in archaeological research, forward although not all data can be handled with equal profundity. This article aims to draw attention to the interesting aspects of a ceramic record, which deviates from the general typological development, and recommends keeping the potential of this source in mind when dealing with interpretations of Bronze Age society. Julie Lolk Moesgård Museum